ACUTE EFFECT OF TWO RESISTANCE EXERCISE INTENSITIES ON RESTING BLOOD PRESSURE IN NORMOTENSIVE INDIVIDUALS - Gamboa Granados, Mariana (2017)
The aim of the study was to determine the effect of resistance-training exercise performed at different intensities on blood pressure (BP) in normotensives. Ten males (age = 38.2±7.0 yrs.; body weight = 75.2±5.4 kg; body height = 169±7.0 cm; resting BP = 116±7.5/71±7.3 mmHg) participated in four resistance-training exercise sessions performed in different days. The first session was used to determine one repetition maximum (1RM) for each resistance-training exercise; the following three sessions were randomly assigned and consisted of: a) seven resistance-training exercises performed at 50% of 1RM (2 sets x 14 reps); b) seven resistance-training exercises performed at 70% of 1RM (2 sets x 10 reps); and c) control condition (35-min quiet resting). Resting BP was measured before exercise, immediately following exercise, and at 10-min intervals for 60-min. Two-way repeated measures ANOVAs showed (p<0.05) that: (1) the systolic BP significantly decreased 20-min following exercise in the 70% 1RM condition compared to the control condition and the measurement before exercise; (2) the diastolic BP was significantly reduced following both exercise intensities compared to the measurements obtained before exercise and compared to the control condition. The acute effects lasted longer following exercise at 50% of 1RM. In conclusion, both resistance-training exercise intensities elicited a post-exercise hypotensive effect in normotensive participants.